Resurrecting Silent Histories: A Journey through the Historical Novels of Kurdish Author Jan Dost - Hashem Ahmadzadeh (Orientalia Suecana)
This article explores the historical novels of Kurdish author Jan Dost, highlighting their role in resurrecting and preserving the silent histories of the Kurdish people. By examining Dost's works through the lens of Georg Lukács's theory of the historical novel, the article delves into how Dost's narratives blend fiction with historical events to cultivate national consciousness and reconstruct Kurdish identity. The study discusses the evolution of the historical novel as a genre and its significance in Kurdish literature, emphasizing Dost's unique contributions. It argues that the nationalist themes and character portrayals in Dost's novels serve as a literary mechanism to reclaim Kurdish history, foster collective memory, and inspire cultural resilience. This analysis aims to understand the reasons behind the success and literary impact of Dost’s works in the broader context of Kurdish and Middle Eastern literature.